EVALUASI KEBIJAKAN PENGADAAN TANAH DI KABUPATEN BANDUNG: (Studi Kasus Pada Proyek Pembangunan Kereta Cepat Jakarta-Bandung) - Prayoga, Indra Aditya; Qodir, Viery Faidhul (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2024)
This research aims to evaluate the success of land procurement policies in the Jakarta-Bandung High-Speed Railway Development Project carried out by the Land Office of Bandung Regency. The method employed is a qualitative approach using a descriptive method that delineates specific circumstances from the emerging facts during the research process without altering the observed phenomena. The evaluation encompasses several indicators, including Inputs, processes, Outputs, and outcomes. Several issues identified include suboptimal planning, constraints in land relocation, land acquisition methods following a Business to Business (B to B) pattern, community dissatisfaction, delayed land payments, land measurement errors, insufficient comprehensive socialization, and inadequate coordination in addressing on-site issues. The research findings indicate that the implementation of Land Procurement Policies for the Jakarta-Bandung High-Speed Railway Development Project by the Land Office of Bandung Regency has yielded moderately satisfying results across most indicators. However, shortcomings exist in slow and unclear information dissemination to the public, low intensity in policy socialization influenced by third parties directly engaging the community, coordination and authority overlap issues between policy implementers and project executors, challenges in facility relocation, emerging land disputes, and additional land route adjustments beyond the initial planning requiring further attention. Hence, it is recommended to enhance information distribution and broader, more intensive policy socialization, improve coordination and collaboration with relevant parties, implement structured dispute resolution, and enhance precision in reviewing planning documents. Keywords: Policy Evaluation; Land Procurement; High-Speed Railway.